2015
DOI: 10.1088/0031-9120/50/4/402
|View full text |Cite
|
Sign up to set email alerts
|

Teaching the absorption of light colours using an artificial rainbow

Abstract: This paper presents an experimental activity based on the absorption of light colours by pigments. The activity is constructed using a stepwise design and offers an opportunity for students and teachers to compare and generalize the interactions between light and pigment colours. The light colours composing an artificial rainbow produced in the classroom are subtracted using a set-up of refractive solutions containing pigments. Symbolic, diagrammatic and realistic representations are provided to explain and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…The studies that strengthen the connection between light colors and pigment colors would be helpful in order to better understand the colors and to design better activities to teach the colors. Recently, related studies in this subject (Babič and Čepič 2009, Yurumezoglu et al 2015, Rosi et al 2016 indicated the importance of this situation from different perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…The studies that strengthen the connection between light colors and pigment colors would be helpful in order to better understand the colors and to design better activities to teach the colors. Recently, related studies in this subject (Babič and Čepič 2009, Yurumezoglu et al 2015, Rosi et al 2016 indicated the importance of this situation from different perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Several works have discussed the design of low cost spectrometer and its usage for in-class learning and simple technology applications in real life [17][18][19][20][21]. This work obtains the absorption spectra of various solutions by directly observing the missing spectral lines of the light source.…”
Section: Absorption Spectramentioning
confidence: 99%
“…One major challenge in this experiment is the wide absorption bands of the solutions and the closely-spaced spectral lines of the Mercury lamp; those spectral lines neighboring the upper or lower band of the absorption spectra will be affected which result in the suppressed intensity of the spectra (Figure 2C, D, and E). The suppression of the transmitted spectra can be attributed to the complex interaction between light and the medium it passes (concentration, optical path, states of matter, and others) [17][18][19][20][21][22][23][24][25]. along with the wavelength associated with the spectra peak is plotted in (E).…”
Section: Absorption Spectramentioning
confidence: 99%
“…A higher numbers of real life situations can be adapted to optics courses to engage students in learning physics. Previous studies attempted procedures on the formation of colours for teaching and learning [9][10][11]. This study using circumzenithal arc advances the availability of colours for stu dents and teachers.…”
Section: Pedagogical Implementations With a Circumzenithal Arcmentioning
confidence: 99%